Meningkatkan Kepekaan Guru tentang Bahasa Inggris dalam Kurikulum Merdeka - Etika Dewi Kusumaningtyas; Eka Fanti Sulistiyaningsih (LPPM AN Nuur, 2022)
Background: The process of internalizing English mostly occurs in the school environment and the teacher acts as a facilitator. The teacher has a big role in the process of internalizing English. Teachers as educators have a role in providing information and media in learning English. Besides that, the teacher's sensitivity in learning and gathering information about English is a major factor. Teachers must be able to increase their sensitivity to English in motivating and providing excellent educational services. In learning activities, the teacher has an important role in making the knowledge and information conveyed acceptable to existing students. The result of this activity is an increase in teacher sensitivity about English related to independent curriculum learning. Increasing the teacher's sensitivity in English will significantly affect the process of learning English at the elementary school level. This increases students' interest and motivation in learning English.